«Non lasciar vivere la malefica» Le streghe nei trattati e nei processi (secoli XIV- XVII) - Corsi, Dinora; Duni, Matteo (Biblioteca di storia, 2008)
Yet another book on witches and witchcraft? Although numerous, studies on this phenomenon that had such a profound influence on the political, social and religious history of the late Middle Ages and the early modern age in Europe can never be enough. At this time the political regimes were actively involved in the witch hunts, not least the Catholic church which was intensely engaged in developing instruments of control aimed at governing and curbing dissent. The book is broken down into thematic sections - rules, treatises and trials, transmission /possession - which reflect the multiplicity of the scientific proposals that have emerged in recent years, and also represent a conscious preliminary orientation of possible readings. At centre stage of the witchcraft show are the witches and their judges, from the theologians and philosophers to the exorcists. As well as addressing actual events, the book also explores the nature of the beliefs and the way in which they were transmitted in the various social strata, and the phenomenon of diabolical possession which conveyed the message of the presence of the devil in the world.